(3TQM CdaGX GdebGeGJ GdMQjQjIs - (3ceGd GdOjf GdbGSe Hf GdbGSe GdhGSWis; (3GdMQjQj,J (B516 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi Lejd BdGFg , hTcQg Ydi LRjd fYeGFg ,hGdUdGI Ydi eMeO eHdZ CHfGFg s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg , CKfGA (B" (3JaSjQ ZQjH GdebGeI GdYTQjf , hgj GdaGQbjI (B" (3bhdg (B: (3hbhdg dh cGf ai YUGi ai GdQhjI Gdbdjd ef GdeGd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfhGfGJ HGdMeQI s
(3Ydi MhGTjgG HYV GdJYdjbGJ s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs